Implementation of Expressive Writing Therapy Through Writing Diary Coping Anxiety in Children Victims of Covid-19 - Wantini Wantini; Suyatno Suyatno; Siti Muthia Dinni (Al-Hayat: Journal of Islamic Education, 2022)
Anxiety experienced by the child can be caused by bad life experiences, like the Covid-19 pandemic. This outbreak leads to the children's mental disorders seen from their changing behavior. This study examines the implementation of Expressive Writing Therapy through diary writing to cope with the child's anxiety of the victims of covid-19. The research method used was a literature study to discuss Expressive Writing Therapy through writing a diary. The data collection technique for this study was documentation through inanimate data sources, like the book of child anxiety, journal of expressive writing, and google scholar. The research showed that Expressive Writing Therapy through diary writing could decrease the level of child's anxiety since their parents passed away due to covid-19. Writing a diary can allow the child to channel their emotions into being more positive and sharpen their brain to be more active. Expressive writing is the way for the child to write freely, so there is no need to be afraid of it. Everything that is felt by the child, like the feeling of mad, happiness, and emotion due to the unpleasant incident, can be distributed into expressive writing. Thus, the child's anxiety can be tackled. Implementation of writing therapy with Islamic psychology becomes self-therapy to improve mental health.